Relation of Hearing Loss with Enlarged Adenoid: A study of 60 cases in BMU (Bangladesh Journal of Otorhinolaryngology, 2026)
This study was done in 60 cases of Enlarge adenoids to see the correlation with hearing impairment. In this study 60 cases were selected from the admit and OPD in the Department of Otolaryngology Head & Neck Surgery, Bangladesh Medical University, Dhaka from October 2021 to March 2023Here patients belonged to different age groups ranging from 3 years to 12 years. Out of 60 cases of enlarged adenoids normal hearing was found In 25 children (41.66%)and hearing impairment was found in 35 children (58.33%) 6-10 years of age group was highest age group with hearing impairment and male, female ratio was 1.7:1 there was 77.14% (27) bilateral and 22.85% (8) unilateral cases. Among 35 OME cases with Enlarged adenoids, 22 cases were gross adenoids 12 were moderate and I was mild adenoids Incidence of hearing loss among gross adenoids were 73.33% moderate adenoids were 48% and mild adenoids were 20%. Maximum hearing loss (41-50 db) was found in case of gross enlarged adenoids, Negative middle ear pressure (-201 to-300 mm of H2O) was also maximum in case of gross adenoids.Bangladesh J Otorhinolaryngol 2026; 32(1): 13-19